Self-presentation of young Singapore celebrities on Instagram - Cheow, Rachel (2016)
This paper aims to examine the underlying meanings behind the self-presentation of young Singapore celebrities on Instagram. Using qualitative content analysis, a total of 540 Instagram posts made by 15 individuals were analyzed. This paper demonstrates the applicability of Goffman’s theory of self-presentation in the analysis of online self-presentation. Findings showed that celebrities exhibited narcissistic tendencies, as suggested from the visual narratives which were generally centered around the self. Celebrities further utilized Instagram as a site for self-promotion through displaying social associations with other high-profile people. Celebrities also engaged in self-branding through strategically crafting out narratives for themselves. Given the ubiquity of social media and the rising popularity of Instagram, it will be sociologically meaningful to gain deeper insights into this phenomenon.